Use of a One-man, Mobile Pressure Chamber in the Treatment of Carbon Monoxide Poisoning. Issue 5705 (9th May 1970) - Norman, J. N.; MacIntyre, J.; Shearer, J. R.; Smith, G.
Abstract : For the past five years a mobile pressure chamber has been used to treat patients suffering from severe carbon monoxide poisoning with oxygen at 2 atmospheres pressure. Of the 25 patients treated, 20 recovered completely and only three died. This apparatus could also be used for hyperbaric oxygen therapy in other conditions for which it is indicated.